Can relaxation exercises improve students’ OSCE grades: a prospective study - Damien Massalou; Jérôme Doyen; Fabien Almairac; Pierre-Simon Rohrlich; Jean-Paul Fournier; Clair Vandersteen; Nirvana Sadaghianloo (Canadian Medical Education Journal)
Introduction: OSCE (Objective Structured Clinical Examination) are a means of assessing health profession students. However, they are a source of stress or anxiety for students. The aim of our study was to improve medical students’ performance during OSCEs by using human performance optimization techniques (HPOT).